IMPROVING STUDENTS’ WRITING SKILL IN DESCRIPTIVE TEXT THROUGH BITS AND PIECES GAME AT THE GRADE VIII 6 OF SMPN 1 TAMBUSAI - Ramanda Rizky (English Language Teaching and Research, 2018)
In the research, the students had problem in writing skill of descriptive text. The aims of this research are to improve students’ writing descriptive text by using Bits and Pieces Game and to find out what factors that influenced the changing of students’ writing skill in descriptive text for students at the VIII 6 Grade of SMPN 1 Tambusai. This research is a Classroom Action Research. The instruments of this research were test, observation, field note, and interview. The participants in this research were the students’ at eighth 6 class consisted of 29 students. The result of this research were Bits and Pieces Game approach could better improve the students’ writing skill in descriptive text at eighth 6 class of SMPN 1 Tambusai. In the based score it showed that their average score was 46.07. It improved to 70.12 in cycle Iand 79.75 in cycle II. The Factors that influenced were Bits and Pieces Game approach assisted almost all meeting that made students were interested in the strategy. In conclusion, Bits and Pieces Game approach can improve students’ writing skill in descriptive text at VIII 6 Grade of SMPN 1 Tambusai.Key words: Bits and Pieces Game strategy, Writing, and Descriptive.